Learning Strategy and Teacher's Role in Meeting 21st Century Students' Competences - Dwi Maryani; Nur Cholidah; Cettra Shandilia Latunusa Ambawani; Darsinah; Wafroturrohmah (Bulletin of Science Education, 2024)
In the 21st hundred years, Indonesia drove the brilliant age by making understudies that fit the requirements and foster the times, through training as well as proper learning endeavors and methodologies through the job of educators in the educational experience. The point of this examination is to break down the job of educators and learning systems in gathering the abilities of understudies in the 21st hundred years. This examination technique utilizes the investigation of writing or libraries utilizing perusing sources like books, diaries, magazines, archives, notes, and other pertinent sources. The consequences of this review can show that the further developed the age then all areas should have the option to follow it, one in the training area should be in a situation to make a brilliant age that matches the improvement of the 21st 100 years, the job of educators and techniques in learning assumes a significant part for schools.